DESIGN AND DEVELOPMENT OF AN E-MODULE FOR VOCABULARY LEARNING IN JUNIOR HIGH SCHOOLS - Syahrianita Syahrianita; Kalsum Kalsum (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This study examines the design, development, and effectiveness of